Project Based Learning (PjBL) Model Integration of Sasak Ethnic Nenun Local Wisdom in Sociology Subjects - Noviana, Mila; Komariah, Siti (Universitas Negeri Medan, 2022)
The PjBL model with the unification of Sasak ethnic nenun local wisdom in Sociology subjects with the nenun topic and social deviation at least gives students a new nuance in learning Sociology so that students are more motivated and have high enthusiasm in learning. The purpose of this study was to integrate the PjBL model with the Sasak ethnic nenun local wisdom in the subject of Sociology. This study used a literature review method, by trying to develop a PjBL learning model that is reviewed from various relevant references. The results of the research was the PjBL model of integrating Sasak ethnic nenun local wisdom in Sociology subjects which can be the basis for educational practice to realize independence, entrepreneurship, responsibility, perseverance, and thoroughness. With the application of local wisdom, it is also able to cultivate the spirit of student learning enthusiasm and students know their own wisdom which is full of good values, empowerment, especially in social and economic aspects, leadership, simplicity, social interaction, hard work, life advice. Added by combining the social media such as Instagram and Tiktok, these are very familiar to students so that it will also affect the Sociology learning process.